Gobierno y administración de la cárcel de Santafé de Bogotá, 1772-1800 (Estudios) - Ariza Martínez, Juan Sebastián (2017)
Based on various case studies, this article describes the main difficulties that prison wardens encountered when governing the royal prison of the court Santafé and how certain inmates were able to break out of jail and challenge the authorities. At the end of the eighteenth century, the prison was in charge of controlling and preventing crime in the city. Nevertheless, in practice, the institution was poorly administered, there were constant jailbreaks, and laws from the peninsula were scarcely enforced.